“Efectos del programa integral del adolescente en conocimientos y actitudes sobre enfermedades de transmision sexual. Punta del este San Martín Tarapoto. Enero – Junio” - Cárdenas Ruíz, Ruth Flor (2002)
This paper is a descriptive study with prospective collection of data retrieved from the students of three colleges State of the fourth and fifth year of secondary education in the District of Yurimaguas. For its execution is used the design descriptive correlates!, using the information in situ based on surveys, is took a shows of 269 students, of which 120 were men and 149 women. About the transmission of the Virus from the human immunodeficiency (HIV), the males responded in a 16.3% by sexual contact and women 21%. Regard to the degree of knowledge of them students before it asks would a student with AIDS or infected with HIV can infect to ·? Fellow of the classroom?, the males responded "NO" to a 75% and 81% women demonstrating a positive attitude. With respect to the degree of knowledge of the students asked do currently have AIDS cure?, they responded with a "NO" 94% of the var...